Aplikasi Augmented Reality (AR) Sebagai Media Pembelajaran Siklus Embrio Manusia Berbasis Android - Safar, Safar; Permadi, Jaka; Utomo, Hendrik Setyo (P3M Politeknik Negeri Tanah Laut, 2018)
Augmented Reality (AR) combining real things and virtual things into 3D’s objects that are appeared on a display screen. AR technology in mobile (smartphones and tablets) can applied for learning media. Specially for Android that have many users from students in Indonesia. The used of mobile among students is still not optimal, because the most of them only use it for communication, social media and playing games. The purpose of development AR based Android for learning media of human embrio cycles is to create a learning environment that is more interactively. From this media the students can interacting directly with cyber objects so that they can learn delightly. The development application performs 3D’s objects and videos virtually from markers that is described as pictures in student’s textbooks. Application will detect markers and then displaying 3D’s models in the screen of the mobile real time and it can performs sounds. The apllication is developed by some softwares like Blender, Unity and Vuforia.